Analysis of the implementation of Political Party Information Systems (SIPOL) from a democratic perspective in the 2019 and 2024 General Elections: Analisis implementasi Sistem Informasi Partai Politik dalam perspektif demokrasi pada Pemilihan Umum 2019 dan 2024 - Aqshadigrama, Muhammad (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2025)
This study aims to examine the aspects of democratic values on the implementation of the SIPOL policy implemented by the KPU to facilitate the process of registration and verification of political parties as candidates for the 2019 and 2024 elections. The method of this writing is qualitative in the form of a library research by using various literature that supports the topic of discussion. Furthermore, the classification of various information collected from various literature sources is carried out. Then it is researched and analyzed qualitatively descriptively, the relationship between data information between one another, so that it can be assembled into a coherent writing. SIPOL as a system that is still relatively new, in its implementation there are several weaknesses that need to be considered and improved for better performance. In the 2019 elections, issues such as technical, validation/verification, and data manipulation occurred a lot. Meanwhile, in the 2024 elections, the central problems were legal/regulatory issues, transparency, and data manipulation, which also dominated. Although, there are a number of these problems, on the one hand, SIPOL turns out to be able to support democratic values. As Robert A. Dahl's view, especially in the aspect of democratic values which emphasizes that an official must be elected through careful and integrity elections, and there must be public freedom in accessing information sources. On the one hand, SIPOL can guarantee the principle of election integrity as a condition for the establishment of democratic values, which is measured on four indicators, namely transparent, honest, accurate and accountable.